2014
DOI: 10.5624/isd.2014.44.4.307
|View full text |Cite
|
Sign up to set email alerts
|

Primitive neuroectodermal tumor of the maxillary sinus in an elderly male: A case report and literature review

Abstract: Primitive neuroectodermal tumor (PNET), which belongs to the Ewing's sarcoma (ES) family of tumors, is mainly seen in children and young adults. PNETs are extremely rare in the maxilla. Here, we report a case of PNET of the left maxillary sinus in an elderly male. Magnetic resonance imaging (MRI) revealed a slightly enhanced solid mass occupying the left maxillary sinus and infiltrating into the retroantral space. A partial maxillectomy was performed. Despite postoperative chemotherapy, follow-up computed tomo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 23 publications
3
10
0
Order By: Relevance
“…In general, the gender distribution of patients with PNET varies among different studies. 1,3,6 We found that women slightly predominate, as distinct from the previously maxillary PNET cases reported by Shah et al in 2014 (male/female ratio of 9:10) ( Table 1). 1 As in our case, there was either as a soft tissue mass or swelling in the most of the reported cases of PNETs of the maxilla in Table 1.…”
Section: Discussionsupporting
confidence: 64%
See 4 more Smart Citations
“…In general, the gender distribution of patients with PNET varies among different studies. 1,3,6 We found that women slightly predominate, as distinct from the previously maxillary PNET cases reported by Shah et al in 2014 (male/female ratio of 9:10) ( Table 1). 1 As in our case, there was either as a soft tissue mass or swelling in the most of the reported cases of PNETs of the maxilla in Table 1.…”
Section: Discussionsupporting
confidence: 64%
“…1,3,6 We found that women slightly predominate, as distinct from the previously maxillary PNET cases reported by Shah et al in 2014 (male/female ratio of 9:10) ( Table 1). 1 As in our case, there was either as a soft tissue mass or swelling in the most of the reported cases of PNETs of the maxilla in Table 1. The patient was admitted to our clinic with progressively increasing, painful swelling on the right side of the face that had been ongoing for 2 months.…”
Section: Discussionsupporting
confidence: 64%
See 3 more Smart Citations